Learners' perspectives on the prevention and management of pregnancy school dropout: a Namibian case - Shiningayamwe, Dorthea Nanghali Etuwete (Frontiers in Sociology, 2023)
Background Namibia has had a problem with the high rate of learner pregnancy and school dropout for many years, despite implementing education sector policy on preventing and managing learner pregnancy. This study aimed to explore the perspectives of school-going learners in Namibia regarding the factors contributing to learner pregnancy and school dropout and propose interventions to address them. Methods This qualitative research employed interpretative phenomenological data analysis, with seventeen individual and ten focus group interviews involving 63 school-going learners: adolescents, pregnant learners, and learner parents. Results and findings Emerging factors driving learner pregnancy and school dropout in rural Namibian schools include older men and cattle herders preying on young girls, long school holidays, the proximity of alcohol sites near school premises, and age restrictions after maternity leave. The learners proposed interventions include prohibiting learners' access to alcohol establishments, strengthening collaborations between stakeholders, sensitizing girls and cattle herders, and ongoing advocacy efforts. Findings indicate community hostility, lack of infrastructure and resources, and learner unawareness. It is essential to mitigate community hostility and raise awareness. Incorporating the perspectives of learners in policy interventions remains crucial for effectively addressing the high rates of learner pregnancy and school dropout in rural Namibian schools.